2002
DOI: 10.1177/002215540205001106
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Method to Determine the Orientation of Collagen Fibers in the Dermis

Abstract: We have developed a quantitative microscopic method to determine changes in the orientation of collagen fibers in the dermis resulting from mechanical stress. The method is based on the use of picrosirius red-stained cryostat sections of piglet skin in which collagen fibers reflect light strongly when epipolarization microscopy is used. Digital images of sections were converted into binary images that were analyzed quantitatively on the basis of the length of the collagen fibers in the plane of the section as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…To further analyze changes occurring in dermis of young and aged individuals in response to loading we utilized a quantitative microscopic method to assess changes in the orientation of collagen fibers using a protocol adapted from Noorlander et al [33]. To quantitatively determine the orientation of collagen fibers in the dermis we converted digital images of sections into binary images and analyzed them on the basis of the measured length of the collagen fibers in the plane of the section as a measure for the fibers orientation [33]. The orientation of collagen fibers in sections of aged skin loaded for 2 and 4 hrs differed significantly when their length was measured compared to control, unloaded, aged skin ( Figure 2, C, D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further analyze changes occurring in dermis of young and aged individuals in response to loading we utilized a quantitative microscopic method to assess changes in the orientation of collagen fibers using a protocol adapted from Noorlander et al [33]. To quantitatively determine the orientation of collagen fibers in the dermis we converted digital images of sections into binary images and analyzed them on the basis of the measured length of the collagen fibers in the plane of the section as a measure for the fibers orientation [33]. The orientation of collagen fibers in sections of aged skin loaded for 2 and 4 hrs differed significantly when their length was measured compared to control, unloaded, aged skin ( Figure 2, C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…The slides were mounted using Fluorescein-FragEL™ Mounting Media. Digitally captured picrosirius red stained images of sections were analyzed with ImageJ (version 1.47; http://rsbweb.nih.gov/ij/) using a protocol adapted from Noorlander et al [33]. Briefly, images were processed using a binary filter, resulting fiber outlines were then fitted with ellipses, then mean length of the major axis was then determined as a measurement for orientation of the bundles of aligned collagen fibers in the plane of the section [33].The mean value of this length parameter was based on three images per section, with a total of 15 specimens per age group, in three serial sections of a specimen was used as a collagen alignment index; the collagen alignment indices of control and loaded skin were compared and differences were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The collagen fibril assembly and collagen fiber bundle formation take place, outside the cell, in inlets formed between fibroblast cell processes in a precise configuration. [16] The alignment of cells and collagen fibers is a result of the forces generated by the cell-mediated gel contraction. [12] And in scars, the unidirectional alignment of collagen fibers occurs in as a sequence of mechanical stress with the fibers getting oriented in the direction of force exerted on the fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Many scientific studies have shown a direct relationship between hernias and a smaller amount of type I and type III collagens in this anatomical region [3,15,24].…”
Section: Discussionmentioning
confidence: 99%